2018
DOI: 10.1007/s12098-018-2767-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Readmission of Pediatric Patients in a Developing Nation

Abstract: The progression of the primary illness and social determinants of pediatric readmissions are important contributing risk factors for readmission in developing countries in pediatric patients. Multicentric studies are needed from this region of the world to include different hospital readmissions rate and to address the issue of potential preventability of pediatric readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…High readmission risk may also be related to other host factors rendering a person susceptible to re-hospitalizations, e.g . chronic illnesses 7 , severe malnutrition or environmental factors 8 . Studies (mainly from developed countries) have shown that 20-40 per cent of readmissions in children are potentially preventable with better clinical management and appropriate discharge planning during the previous admission along with good post-discharge follow up and care with early intervention in domiciliary setting 9 - 11 .…”
mentioning
confidence: 99%
“…High readmission risk may also be related to other host factors rendering a person susceptible to re-hospitalizations, e.g . chronic illnesses 7 , severe malnutrition or environmental factors 8 . Studies (mainly from developed countries) have shown that 20-40 per cent of readmissions in children are potentially preventable with better clinical management and appropriate discharge planning during the previous admission along with good post-discharge follow up and care with early intervention in domiciliary setting 9 - 11 .…”
mentioning
confidence: 99%